Tourism security and AI-based communication management of tourist interest in Pari Island - Rohim, Syaiful; Darmawati, Desak Made; Latief, Jamil; Alimudin, Muhamad (Faculty of Communication Sciences Universitas Padjadjaran, 2025)
Tourism is a crucial factor in national development, and destination security is an increasingly influential consideration for tourists' travel decisions, especially in the post-pandemic era. Concurrently, digital communication facilitated by artificial intelligence (AI) offers new potential to enhance the credibility of information and improve tourists' interactions with destinations. This study explores the impact of security in tourism on tourist demand and examines the mediating role of AI-based digital communication policies for Pari Island, Indonesia, in the Jakarta Thousand Islands. The study adopts a quantitative approach through the use of an explanatory sample of 100 local and international tourists who have visited or are visiting Pari Island. Data were collected using a standardized questionnaire and analyzed by path analysis using the SmartPLS software. Findings reveal security in tourism has a statistically significant positive effect on tourist interest (β = 0.32; p < 0.01) and even an indirect effect through AI-based digital communication (β = 0.41; p < 0.01). The use of digital communication supported by AI in augmenting the role it plays in the determination of tourists' decision-making. The study concludes that the essence of trust enhancement and destination appeal lies in integrating solid destination security and smart digital communication systems. The study also recommends that policymakers and tourism administrators improve safety while embracing digital innovations to initiate change and foster sustainable tourism development in Indonesia.